UMP Alumni Association distributes hand sanitisers to frontliners - Mohd Ferdaus, Musa (2020)
As an appreciation to the frontliners who have been working tirelessly around the clock to fight the Covid-19 outbreak, the UMP Alumni Association (Alumni UMP) contributed hand sanitisers to UMP Security Division and Kuantan District Health Office on 3 April 2020.